Compensation or cosmopolitan attitudes: Explaining leisure travel of Nordic urbanites. (October 2020) - Czepkiewicz, Michał; Klaas, Valentina; Heinonen, Jukka
Highlights: A softGIS study of factors explaining long-distance travel of young adults (25 to 40 y.o.) living in Helsinki, Finland and Reykjavik, Iceland is presented. Neighborhood greenness was related to a higher number of trips in Helsinki, but not in Reykjavik. In Helsinki, people mismatched with their residential neighborhoods in terms of greenness travel more domestically than other groups. Geographical differences in the frequency of trips abroad are largely explained by spatial clustering of cosmopolitan attitudes in the city centres. Inadequacies resulting from densified urban environments should be minimized to reduce compensatory travel, but the results do not challenge densification policies in general. Abstract: Inner cities have been recently linked to a higher volume of long-distance travel for leisure purposes of their residents when compared to suburban and rural areas. The compensation hypothesis proposes that this difference results from urban residents' tendency to travel away to compensate for poor access to green spaces or to escape urban stressors. This paper tests two versions of this hypothesis using two softGIS surveys of young adults living in the capital regions: Helsinki in Finland and Reykjavik in Iceland. We also examine an alternative hypothesis of cosmopolitan attitude as the explaining factor. We consider the levels of consonance or dissonance between the residential preferences and the GIS-measured characteristics of residential environments, attitudes towards travel, and socio-demographic and lifestyle characteristics of respondents. We found weak and contextual support for the compensation hypothesis: neighborhood greenness was related to the number of trips in Helsinki, but not in Reykjavik. In both cities, the trend of increasing trip numbers along with the distance to the city center was explained mainly by the spatial clustering of cosmopolitan attitudes in the city centres. Private car ownership and summer cottage access were also significant predictors of domestic trips frequency. Overall the results suggest that the compensation effect is neither exclusive nor the most plausible explanation for differences in travel patterns between urban dwellers. Still, it might be at play in some circumstances. The results do not challenge compact city policies but suggest paying attention to additional travel demand due to the inadequacies of urban environments.